PENERAPAN BERMAIN BASOVI UNTUK MENINGKATKAN HASIL BELAJAR PASSING BAWAH BOLA VOLI PADA SISWA KELAS V SD NEGERI 1 JUMO KABUPATEN GROBOGAN TAHUN PELAJARAN 2012/2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study was to improve learning outcomes Passing under the fifth grade students of SD Negeri 1 Jumo Grobogan Academic Year 2012/2013. This research is a classroom action research was conducted in two cycles. In two such cycles in each cycle consisting of four stages, namely planning, implementation, observation, and reflection. The subjects in this study are all fifth grade students of SD Negeri 1 Jumo. Data analysis technique used is the percentage and passing a test instrument under the Basovi game. The results showed an increase in student learning outcomes in the first cycle achievement through the implementation of the material aspects of koqnitif reached 82%, 72% mancapai affective aspect, psychomotor aspects of 78%, the average grade has increased to 76 from the previous 68, but the mastery class only at 63% only. So stated that in the first cycle of learning has not been successful.While in the second cycle of achievement material aspects koqnitif reached 87%, reaching 74% affective aspect, psychomotor aspects of 86%, the results of student learning has increased to 84 and the percentage of student mastery has reached 85%. So that in the second cycle of learning can be said that the study was successful. Thus action playing Basovi Application to Improve Learning Outcomes Volleyball Passing Down In Fourth Grade Students of SD Negeri 1 Jumo Grobogan Academic Year 2012/2013 can be said to be successful.